Diffusion-controlled solid-state reactive sintering of Nd:YAG transparent ceramics. Issue 9 (November 2015) - Liu, Binglong; Li, Jiang; Ivanov, Maxim; Liu, Wenbin; Ge, Lin; Xie, Tengfei; Kou, Huamin; Zhuo, Shangjun; Pan, Yubai; Guo, Jingkun
Abstract: Diffusion-controlled solid-state reactive sintering is one of the most important steps in fabrication of highly transparent Nd:YAG ceramics using commercial oxide powders as starting materials. The difference in raw powders, especially for the characteristic of Y2 O3 powder, will seriously influence the sintering behavior and finally lead to the large difference in microstructure and optical property. Thus, interactions between commercially available α-Al2 O3 submicron particles and severely agglomerated Y2 O3 nanoparticles during vacuum sintering were investigated in details in the present paper. Upon examining the influence of solid-state reactive diffusion in Nd:YAG ceramics, by optimizing the sintering parameters, highly transparent Nd:YAG ceramics were fabricated by solid-state reactive sintering of Y2 O3, α-Al2 O3 and Nd2 O3 powders. The in-line transmittances of the ceramics achieved 83.8% and 81% at 1064 nm and 400 nm, respectively.